OACoder: Postcode Coding Tool. (8th October 2013) - Adnan, Muhammad; Singleton, Alex; Longley, Paul A.
Geodemographic classifications are small area classifications of social, economic and demographic characteristics. The Output Area Classification (OAC) is a free geodemographic classification. It is an Office of National Statistics validated measure that summarises neighbourhood conditions at the Output Area Level across the United Kingdom. Linkage of these valuable statistics has been problematic for users more used to address records that are georeferenced using unit postcodes. OACoder resolves this problem by allowing users to link corresponding OAC codes to each of the postcode addresses. OACoder is an open source software, and it is developed and tested to work on different versions of windows operating systems. It is stored in Figshare. The source code of the OACoder is stored in SourceForge. As open source software, OACoder has reuse potential across a range of applications. The functionality of OACoder can be extended to work with the new version of OAC (2011 OAC). It is also possible to reuse the source code and extend the functionality to work on different operating systems other than Windows. Different components of the software can be reused for the purpose of reading/writing CSV files and handling large data sets.